Influenza vaccination coverage rates in five European countries during season 2006/07 and trends over six consecutive seasons - Szucs Thomas D; Schwenkglenks Matthias; Blank Patricia R (BMC, 2008)
Abstract Background The objectives of the survey were to identify the level of influenza vaccination coverage in five European countries between 2001 and 2007, to understand the drivers and barriers to vaccination, to assess vaccination intentions for the winter 2007/08 as well as major encouraging factors for vaccination. Methods Between 2001 and 2007, representative household surveys were performed with telephone or mailed (France) interviews of individuals aged 14 and above. The questionnaire used in the UK, Germany, Italy, France and Spain was essentially the same in all seasons. The data were subsequently pooled. Four target groups were defined for the analysis: 1) persons aged 65 years and over; 2) persons working in the medical field; 3) chronically ill persons and 4) combined target group composed of individuals belonging to one or more of the previous groups 1, 2 or 3. Results In 2006/07, vaccination coverage was, 25.0% in UK, 27.4% in Germany, 21.8% in Spain, 24.2% in France and 24.4% in Italy. During six influenza seasons (2001-2007), vaccination coverage showed a slight positive trend in the five countries (p ≤ 0.0001). In the elderly (≥ 65 years), across all countries, no significant trend was seen; the vaccination rate decreased non-significantly from a peak of 64.2% in season 2005/06 to 61.1% in season 2006/07. The most frequent reason for getting vaccinated was a recommendation by the family doctor or nurse (51%), and this was also perceived as the major encouraging factor for vaccination (61%). The main reason for not getting vaccinated was feeling unlikely to catch the flu (36%). Conclusion In the UK, Germany and Spain, influenza vaccination coverage rates in season 2006/07 dropped slightly compared to the previous season. However, a trend of increasing vaccination coverage was observed from 2001/02 to 2006/07 across Europe. The family doctor is the major source of encouragement for individuals getting vaccinated. Efforts to overcome the barriers to vaccination need to be put in place to reach the WHO objective of 75% coverage in the elderly by 2010. This is a major challenge to be faced by governments, healthcare workers and healthcare organisations.